Feasible structure-modification strategy for inhibiting aggregation-caused quenching effect and constructing exciton conversion channels in acridone-based emitters. Issue 19 (29th April 2019) - Wan, Qing; Zhang, Bing; Tong, Jialin; Li, Yin; Wu, Haozhong; Zhang, Han; Wang, Zhiming; Pan, Yuyu; Tang, Ben Zhong
Abstract : The introduction of multiple rotors donors and benzonitrile group in ADOs would increases effectively OLED emitters' performance by inhibiting aggregation-caused quenching effect and constructing exciton conversion channels. Abstract : Acridone (ADO) is an anthracene-based derivative that plays an important role in the construction of organic light-emitting diode emitters. However, ADO suffers from an aggregation-caused quenching (ACQ) effect because of its strong intermolecular stacking and tendency to form excimers. In this work, we appended some electron-donating moieties with different rotors and substitution patterns on ADO to prepare six ADO-based derivatives. In addition, a benzonitrile group was introduced onto the nitrogen atom of the ADO unit to fabricate a high-energy charge-transfer (CT) state that formed a reverse intersystem crossing (RISC) channel. Systematic spectral measurements revealed that the rotors effectively suppressed the ACQ effect. In addition, aggregation-enhanced emission (AEE) was observed for the ADO derivatives modified with triphenylamine (TPA) because of the existence of multiple rotors and propeller-like conformation in TPA block. Theoretical calculations and the performance of electroluminescent devices containing the derivatives confirmed that the exciton conversion channel was constructed at the high-energy level and activated during device operation. Although the performance of these ADO-based derivatives was not ideal in terms of efficiency, the results confirmed the feasibility of this structure modification strategy to simultaneously inhibit the ACQ effect and construct excitons conversion channels.